2007
DOI: 10.1352/1934-9556(2007)45[174:basesw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Among Special Education Students With Intellectual Disabilities: Differences in Social Adjustment and Social Skills

Abstract: Harassment and bullying among 186 students with intellectual disabilities, ages 12 to 21 years, in special education schools were examined. The differences between bullies and victims in terms of social adjustment and social skills were investigated. No prototypes characterizing differences in social skills were found between the three subgroups: victim, bully, and victim-bully. However, bullies and victim-bullies exhibited significantly higher levels of challenging behaviors, such as temper tantrums, unruly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 13 publications
1
41
0
4
Order By: Relevance
“…This is a common finding in the relevant literature (Kourmousi, 2012;Cassidy et al, 2003, Espinosa, 2002Saarni, 2001, Mundy & Re-attendance of the same grade and need for special education assistance also predicted lower scoring in our study's scale. This can be explained by the findings of other studies (Reiter & Lapidot-Lefler, 2007;Jahoda, Pert, & Trower, 2006;Luckasson et al, 2002) which have shown that delay in aspects of cognitive development affects the socio-emotional development as well. As researchers state, populations with intellectual disabilities are deprived in social adjustment and social skills and competencies (Reiter & Lapidot-Lefler, 2007;Jahoda, Pert, & Trower, 2006;Luckasson et al, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…This is a common finding in the relevant literature (Kourmousi, 2012;Cassidy et al, 2003, Espinosa, 2002Saarni, 2001, Mundy & Re-attendance of the same grade and need for special education assistance also predicted lower scoring in our study's scale. This can be explained by the findings of other studies (Reiter & Lapidot-Lefler, 2007;Jahoda, Pert, & Trower, 2006;Luckasson et al, 2002) which have shown that delay in aspects of cognitive development affects the socio-emotional development as well. As researchers state, populations with intellectual disabilities are deprived in social adjustment and social skills and competencies (Reiter & Lapidot-Lefler, 2007;Jahoda, Pert, & Trower, 2006;Luckasson et al, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, research by Reiter and Lapidot -Lefler (2007) showed that the victimization of pupils with mental retardation occurs at the same frequency in both inclusive and special ISSN 2377-3936 2017 educational contexts. This finding is in contradiction with other surveys which state that the rates of victimization of students with mental retardation are 2 to 3.5 times higher in special schools than in inclusive ones (Martlew & Hodson, 1991;Morrisson, Furlong, & Smith, 1994).…”
Section: Intellectual Disability (Mental Retardation)mentioning
confidence: 99%
“…Σε έρευνα που πραγματοποίησαν οι Reiter & Lapidot-Lefler (2007) σε δυο σχολεία ειδικής αγωγής βρήκαν ότι το 83% του δείγματος εκφοβιζόταν, ενώ τα φαινόμενα που παρατηρούνταν με φθίνουσα συχνότητα είναι: «τους είχαν βρίσει, είχαν γελάσει μαζί τους, τους είχαν πει άσχημα πράγματα, τους είχαν χτυπήσει, τους είχαν σπρώξει, τους είχαν απειλήσει πως θα τους βλάψουν, τους είχαν κλωτσήσει, τους είχαν τσιμπήσει, τους είχαν ωθήσει να κάνουν πράγματα που δεν ήθελαν, τους είχαν ακουμπήσει σεξουαλικά και τέλος τους είχαν κλέψει». Ο σχολικός εκφοβισμός εις βάρος των μαθητών με αναπηρίες που εντοπίζεται συχνότερα είναι ο λεκτικός, δηλαδή ο χλευασμός και τα προσβλητικά σχόλια που επικεντρώνονται στις αναπηρίες τους (Bunch & Valeo, 2004.…”
Section: μορφές εκδήλωσης του εκφοβισμούunclassified
“…Είναι γενικά αποδεκτό μεταξύ των ερευνητών ότι οι μαθητές με ειδικές εκπαιδευτικές ανάγκες έχουν υψηλότερα ποσοστά σχολικού εκφοβισμού συγκριτικά με τους μαθητές τυπικής ανάπτυξης (Holzbaouer, 2008, Mishna, 2003, Reiter & Lapidot-Lefler, 2007, Rose, Monda-Amaya & Espelage, 2010. Σε άλλη μελέτη, όπου εξετάστηκαν πολλές κατηγορίες μαθητών με αναπηρίες, δηλώνεται πως οι μαθητές με μαθησιακές δυσκολίες, όπως και οι μαθητές με σωματικές αναπηρίες, παχυσαρκία, ημιπληγία, διαβητικοί, με σύνδρομο ελλειμματικής προσοχής αλλά και με τραύλισμα έχουν περισσότερες πιθανότητες να υποστούν εκφοβισμό σε σχέση με τους μαθητές τυπικής ανάπτυξης (U.S. Department of Health & Human Services).…”
Section: ποσοστά και παράγοντες θυματοποίησηςunclassified